Effect of Centella asiatica (Gotu kola) as feed additive on blood profile, egg quality and gut microbial contents of laying birds - Olabisi A Ajibade; Grace Oluwatoyin Tayo; Martha Dupe Olumide; Adeyinka Oye Akintunde (Aceh Journal of Animal Science, 2023)
The use of medicinal plants is gaining popularity all over the world; hence there is a need to exploit various plants that could be of economic importance to animal. Centella asiatica is one of such plants that are underutilized. This study was conducted to investigate the utilization of Centella asiatica leaf meal as feed additive in layers production. The study was carried out in two phases, the grower phase and layer phase. A total number of 150 birds were used at 10 birds per replicate of 3 replicates per treatments of a total of 5 treatments. The diets contained Centella asiatica leaf meal at five levels of inclusion 0.0%(control), 0.2%,0.4%, 0.6% and 0.8% at grower and layer phases. The experiment was arranged in a completely randomized design layout. Hence, Centella asiatica leaf meal showed potentials of being natural growth promoting additive. Centella asiatica leaf meal used as additive at 0.2-0.8% inclusion level significantly increased (p0.05) final live weight, weight gain and improved feed conversion ratio at grower and layer phases. 0.6% inclusion of CALM increased packed cell volume (PCV) and haemoglobin (Hb) and 0.8% inclusion of CALM increased red blood cell (RBC) values at grower phase.  At layer phase, 0.6% inclusion of CALM significantly increased (p0.05) PCV and RBC while 0.8% CALM significantly increased (p0.05) haemoglobin (Hb) value but there was significant reduction (p0.05) in total bacteria count (TBC) at the caecum and ileum of birds at grower and layer phases respectively.  0.8% CALM inclusion resulted in significantly highest (p0.05) weight of eggs, hen day egg production at 4th, 8th and 12th week in lay. 0.6% inclusion of CALM significantly improved (p0.05) egg weight and yolk weight score at 12th weeks in lay. The inclusion of Centella asiatica leaf meal in the diets of Isa Brown grower and laying phases, resulted in better blood profile, haematological and serum biochemical parameters, gut microbial population, egg production and quality of laying hens.